Evidentiality in Hindi: A Typological View - Sigorskiy, Alexander A. (Lingua Posnaniensis, 2013)
The point of departure for the present paper is the status of the bare participial form as inherited from MIA (Middle Indo-Aryan) by early N IA (New Indo-Aryan) with its stative force. It is a very well known phenomenon in the contemporary IA languages that the past participle can be extended by a past participle form based of the verb to be (e.g. MSH – Modern Standard H indi – huā). It is also noticeable that not all N IA languages allow such extension and that several languages developed further, and reinterpreted the extended forms. T he aim of the present paper will be to demonstrate how the stative participles developed in two branches of IA, namely E astern and W estern P ahari.1 The data for this preliminary research has been excerpted from W estern P ahari inscriptions (Chhabra 1957), Eastern Pahari inscriptions (Pokharel 1974; Cauhān 2008; Joshi 2009), reference grammars and folk texts.